Offline Store China "Oh! Some" in Jabodetabek: Brand Image, Price, Product Quality and Service to Purchase Decisions - Ari Nugroho, Surya; Wulandari, Nuri; Maju Simatupang, Batara; Haryanti, Enny (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Online shopping trends in Indonesia saw rapid growth during the COVID-19 pandemic. However, post-pandemic, interest in offline shopping increased again, especially in modern offline stores that combine modern store with lifestyle. This resurgence is driven by the need for direct product interaction, personalized customer service, and enjoyable shopping experiences that online shopping cannot be fully replaced by online shopping. The emergence of modern offline stores like OH!SOME, Miniso, Niceso, Usupso, Minigood, and Daiso, particularly in the Jabodetabek area, has led to intense competition to attract consumers. OH!SOME, as one of foreign retailer from KK Group China, has rapidly expanded in Indonesia with innovative marketing strategies and attractive store concepts. This research aims to analyze the influence of brand image, price, product quality, and service quality on purchasing decisions at OH!SOME offline stores in the Jabodetabek area. This research uses a quantitative method with Structural Equation Modelling - Partial Least Square (SEM-PLS) analysis technique using Smart PLS 4. The research sample consists of consumers who have made purchases at OH!SOME offline stores and live in the Jabodetabek area. The results show that the four independent variables have a positive and significant influence on purchasing decisions, with p-value < 0.05 and t-value > 1.96. Brand image has the greatest influence with a path coefficient of 0.287, followed by service quality and product quality, both having a path coefficient of 0.252, and price with a path coefficient of 0.171. These findings indicate that to increase purchasing decisions, OH!SOME needs to continue strengthening its brand image, improving service quality, maintaining product quality, and implementing competitive pricing strategies.